2019
DOI: 10.18097/pbmc20196503202
|View full text |Cite
|
Sign up to set email alerts
|

Mullerian inhibiting substance type II receptor as a potential target for antineoplastic therapy

Abstract: The review considers properties of the type II anti-Mullerian hormone receptor (mullerian inhibiting substance receptor type II, MISRII), a transmembrane sensor with its own serine/threonine protein kinase activity, triggering apoptosis of the Mullerian ducts in mammalian embryogenesis and providing formation of the male type reproductive system. According to recent data, MISRII overexpression in the postnatal period is found in cells of a number of ovarian, mammary gland, and prostate tumors, and anti-Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…AMHRII (also known as MIS receptor II) acts as a transmembrane sensor with serine/threonine protein kinase activity ( Rak et al 2019 ). It has been demonstrated that free AMH exclusively binds to AMHRII ( Mishina et al 1996 , Josso et al 2001 ), and the receptor regulates gene transcription via three mechanisms ( Rak et al 2019 ). First, when AMH binds to AMHRII, it forms a receptor complex with AMHRI.…”
Section: Constantly Explore the New Potential Of Amh/amhriimentioning
confidence: 99%
See 4 more Smart Citations
“…AMHRII (also known as MIS receptor II) acts as a transmembrane sensor with serine/threonine protein kinase activity ( Rak et al 2019 ). It has been demonstrated that free AMH exclusively binds to AMHRII ( Mishina et al 1996 , Josso et al 2001 ), and the receptor regulates gene transcription via three mechanisms ( Rak et al 2019 ). First, when AMH binds to AMHRII, it forms a receptor complex with AMHRI.…”
Section: Constantly Explore the New Potential Of Amh/amhriimentioning
confidence: 99%
“…Subsequently, intracellular Smad-proteins (R-SMads1/5/8) detach from the receptor complexes, allowing several proteins to enter the nucleus to regulate gene expression ( Josso et al 2001 , Bedenk et al 2020 ). In the nucleus, Smad proteins can either bind to DNA at Smad recognition sites (leading to transcriptional activation) or form complexes with other transcription cofactors that specifically affect the expression of target genes ( Pankhurst et al 2016 , Rak et al 2019 ). Second, binding of AMH to the type II receptor increases the content of free β-catenin in the cytoplasm, which then enters the nucleus together with lymphoid enhancer factor 1, upregulating the transcription of target genes ( Rak et al 2019 ).…”
Section: Constantly Explore the New Potential Of Amh/amhriimentioning
confidence: 99%
See 3 more Smart Citations